Study on Feminist Thoughts in Top Girls - Shi, He (Transactions on Social Science, Education and Humanities Research, 2024)
The development of western feminist literature is close to the development of western feminist movements and theories. With the aid of the theories of Simone de Beauvoir and Irigaray, the paper intends to explain Top Girls written by Caryl Churchill from the way of feminism. It explores the alienation and oppression of feminists themselves, and points out feminists fall into imitating patriarch pattern unconsciously. It manifests the characteristics of postmodern feminism of feminist literature.